Organisatorisk stolthet och arbetstillfredsställelse inom Luleå kommun : En studie kring hur anställda inom Luleå kommun påverkas av arbetsgivarvarumärket Spela roll - Broms, Hannah; Nyström, Alicia (Luleå tekniska universitet, Institutionen för hälsa, lärande och teknik, 2022)
In today's society, an employer brand is important both for establishing oneself as a goodemployer but also for retaining competent staff. This is a quantitative study with the aim ofexamining the difference of an employer brand within Luleå Kommunon employees and theirfeelings about Luleå Kommun as an employer and workplace, at group level in pride and worksatisfaction. The data were collected through a repeated cross-sectional survey that Luleåkommun sent out to 10 and 20 percent of its employees during the years 2020 and 2022,respectively. A total of 996 people responded to the survey (n = 369 in 2020; n = 627 in 2022).The data were analyzed using descriptive statistics and Mann-Whitney U-tests. The resultsshowed that pride has increased at the group level in Luleå kommun from 2020 to 2022.Satisfaction with their work and workplace has also increased at the group level in Luleåkommun from 2020 to 2022. While the employer brand Spela roll has aimed to increase supportand sense of belonging for employees, this study, however, can not draw any conclusions aboutcausality to attribute the aforementioned changes to the employer brand.